2018
DOI: 10.3390/ijerph15081783
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression and Subsequent Autoimmune Diseases in Taiwan

Abstract: Postpartum depression (PPD) is one of the most common examples of postnatal morbidity, but the subsequent risks of autoimmune diseases in patients with PPD have yet to be fully investigated. This nationwide population-based study utilized data of the National Health Insurance Research Database of Taiwan for the period from 1996 to 2013. In total, 45,451 women with primiparity were identified. Among them, 542 patients with PPD were enrolled as a study group while 2165 matched patients without PPD were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…An effect of the duration of depression was seen, with a higher incidence rate for RA observed in the 3–5 and more than 5 year periods after onset of depression. Postpartum depression and subsequent risk of RA has also been studied in this dataset, with an elevated risk also found (adjusted hazard ratio 2.62, 95% CI 1.28–5.39) [19].…”
Section: Epidemiologic Evidence Of Depression As a Risk Factor For Rhmentioning
confidence: 99%
“…An effect of the duration of depression was seen, with a higher incidence rate for RA observed in the 3–5 and more than 5 year periods after onset of depression. Postpartum depression and subsequent risk of RA has also been studied in this dataset, with an elevated risk also found (adjusted hazard ratio 2.62, 95% CI 1.28–5.39) [19].…”
Section: Epidemiologic Evidence Of Depression As a Risk Factor For Rhmentioning
confidence: 99%
“…Our results are consistent with studies showing women with perinatal mental illness are at elevated risk for autoimmune disease. In a population-based cohort of 2707 primiparas in Taiwan, Lin et al 4 showed women with postpartum depression had increased risk, compared to those without postpartum depression, for autoimmune disease (aHR 1.61, 95% CI 1.30–1.99). Likewise, among 148 Dutch women, Bergink et al 5 found women with postpartum psychosis had a higher rate of autoimmune thyroid disease than their peers (19% vs 5%).…”
Section: Discussionmentioning
confidence: 99%
“…There is preliminary evidence that women with perinatal mental illness are at elevated risk for autoimmune disease. 4 , 5 Some authors have postulated that perinatal mental illness is itself an autoimmune disease. 6 Autoimmune diseases are a clinically heterogenous group of disorders defined by an abnormal immunologic reaction to self-antigens resulting in tissue damage and dysfunction of specific organs or entire body systems, including the endocrine, gastrointestinal, liver, neurological, and rheumatological systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grupa tajvanskih autora predlaže ispitivanje koncentracije tiroidnih hormona kod pacijentkinja sa postpartalnom depresijom [21].…”
Section: Diskusijaunclassified